Bridging the Gap: Understanding the Differing Research Expectations of First-Year Students - Meg Raven (Evidence Based Library and Information Practice, 2012)
Objective – The project sought to understand the research expectations of first-year students upon beginning university study, and how they differed from the expectations of their professors, in order to provide more focused instruction and work moreeffectively with professors and student support services. Methods – A survey of 317 first-year undergraduate students and 75 professors at MountSaint Vincent University in Halifax, Nova Scotia, was conducted to determine what eachexpected of first-year student research. Students were surveyed on the first day of theterm in order to best understand their research expectations as they transitioned fromhigh school to university. Results – The gulf between student and professor research expectations was found to beconsiderable, especially in areas such as time required for reading and research and theresources necessary to do research. While students rated their preparedness foruniversity as high, they also had high expectations related to their ability to use nonacademicsources. The majority of professors believed that students are not prepared todo university-level research, do not take enough responsibility for their own learning,should use more academic research sources, and should read twice as much as studentsbelieve they should. Conclusions – By better understanding differing research expectations, students can beguided very early in their studies about appropriate academic research practices, andlibrarians and professors can provide students with improved research instruction.Strategies for working with students, professors, and the university community arediscussed.